Association between delayed invasive blood pressure monitoring and all-cause mortality in intensive care unit patients with sepsis: a retrospective cohort study - Li Xiao; Pu Shen; Xue Han; Yi Yu (Frontiers in Medicine, 2024)
PurposeHaemodynamic management is essential in sepsis management. Invasive blood pressure (IBP) monitoring is the gold standard for blood pressure (BP) assessment. Here, we identified the most advantageous time frame for IBP monitoring to mitigate adverse outcomes in patients with sepsis.MethodsWe included data on patients with sepsis from the Medical Information Mart for Intensive Care IV database. The primary endpoints comprised 28-and 90-day mortality rates, whereas secondary endpoints were acute kidney injury (AKI) rates and continuous renal replacement therapy (CRRT) requirement. To confirm our findings’ robustness, we performed multivariable Cox regression and logistic regression models, augmented by propensity score matching (PSM).ResultsOf 18,326 patients hospitalised for sepsis, 9,056 (49.42%) and 9,270 (50.58%) were included in the early and delayed IBP-monitoring groups, respectively. Our multivariable Cox regression models revealed 20 and 21% significant increases in 28-and 90-day mortality in the delayed IBP monitoring group, respectively [hazard ratios (95% confidence intervals) = 1.20 (1.11–1.31) and 1.21 (1.12–1.31), respectively; both p < 0.001]. Moreover, significant increases were noted in AKI, CRRT and mechanical ventilation requirement risks in the delayed IBP monitoring group [odds ratios (95% confidence intervals) = 1.44 (1.34–1.56), 1.50 (1.26–1.78) and 1.79 (1.67–1.92), respectively; both p < 0.001]. PSM further confirmed the validity of our findings. Delayed IBP monitoring prolonged intensive care unit (ICU) stay without extending vasopressor use duration.ConclusionProlonged delay in IBP monitoring (≥3 h) may increase mortality risks in ICU patients with sepsis. Nevertheless, early IBP monitoring may reduce AKI, CRRT and mechanical ventilation requirement risks and shorten ICU stay. However, these results warrant further validation through randomised controlled trials.